THE RELEVANT OF PSYCHOLOGICAL CAPITAL ON ADAPTIVE PERFORMANCE BEHAVIOR AMONG YOUNG PROFESSIONALS: A CONCEPTUAL STUDY IN MALAYSIA CONTEXT - Ummi Kalsum Binti Hassian; Rachel Samuel A/P Samuel (International Journal of Accounting, Finance and Business, 2021)
Adaptive Performance Behaviour, the focus of this study, has receive much attention as new workplace demands require flexible employees who are tolerant of uncertainties and can successfully perform in dynamic, competitive environments. This study examines the relevance of psychological capital on adaptive performance behaviour in the context of young professionals in the Malaysian service sector. Adaptive performance behaviour is highly relevant in firms where the business models and management are volatile due to technological or market evolution and environmental changes. In addition, the study also examines how psychological capital can enhance adaptive performance behaviour. Data will be collected from 103 young professionals in the Malaysian service sectors via survey questionnaire adopted from related literature and interviews from practitioners. Purposive sampling is a technique which involves the researcher choosing sampling units based on existing, scientific knowledge or the researcher’s professional judgement. The sampling frame of this study includes all young professionals within the service sectors listed in the Federation of Manufacturing Malaysia Industry (FMM) directory 50th edition. The data collected will be analysed using structural equation modelling via Smart PLS. Self Determination Theory is used as the underpinning theory for this study as this theory offers a well-supported conceptualization which proposes that motivation is best represented by conceptually distinct, yet complementary, types of behavioral regulations experienced by individuals to varying degrees.